The Correlation Between Digital Literacy and Students Reading Comprehension at Eleventh Grade of Senior High School 1 Jambi - Putri Adinda Agustiani KS (Universitas Batanghari Jambi, 2022)
This research aims to find The Correlation between Digital Literacy and Students’ Reading Comprehension at Eleventh Grade of Senior High School 1 Jambi. The design of this research is Descriptive Research method with Correlation Approach. This research conducted in Senior High School 1 Jambi. There were 32 respondents as sample of this research. The data in this research were collected by test and questionnaires. The test consisted of 20 multiple choice questions and questionnaires consisted of 16 statements in close- ended questionnaires. After collecting the data, the researcher analyzed the data to find the results by using Descriptive Statistics and Pearson Product Moment Correlation Formula. The result of this research showed that there is correlation between Digital Literacy and Students' Reading Comprehension at Eleventh MIPA 5 where as significant value obtained 0,04. Therefore, in hypothesis 0.05 < hypothesis is accepted and 0.05 > hypothesis is rejected. As for the category of Digital Literacy and Students Reading Comprehension, Digital Literacy is at very high category. Meanwhile for Students' Reading Comprehension is at good category.